Does deafness spell disaster? An analysis of the written English levels of deaf children in the Nelson Mandela Metropole, South Africa - Weir, Carolyn; Ayliff, Diana (Faculty of Education, University of the Free State, 2014)
This article presents the findings of an empirical comparative study in the Nelson Mandela Metropole investigating the difference between the written English of deaf children and the written English of hearing children and makes recommendations on how to improve the writing of deaf children. The psycholinguistic approach was used for the theoretical framework. Within the framework of psycholinguistics, the acquisition and development of language and writing are discussed from the perspective of (1) emergent literacy and (2) the critical period hypothesis. The findings of this research indicate a significant difference between the writing of the deaf and hearing children who participated in this study. In order for deaf children in South Africa to develop their writing, immediate government assistance is necessary in order to implement newborn screening country wide followed by medical and/or language-based intervention to minimise the impact of deafness on the language and writing abilities of deaf children. This is an essential foundation on which parents and teachers can build in helping deaf children reach age-appropriate levels of written English.
Keywords: Deaf; Children; English; Writing; Emergent literacy; T-units; South Africa; Nelson Mandela Metropole